2020
DOI: 10.1002/apj.2449
|View full text |Cite
|
Sign up to set email alerts
|

Position and feedback for digital microfluidic system based on light intensity information

Abstract: The digital microfluidic system based on electrowetting on dielectric is a new technology that can control microliter droplets within the plane. Because of layout, fabrication, and driving uncertainties, feedback control schemes must be designed and implemented to ensure safety and reliability of digital microfluidic system for practical application. The basis for feedback is to realize the accurate droplet location. So, there is a strong need for the development of a digital microfluidic system integrated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Under the condition that the droplets can move successfully every time they are driven, the whole merging duration is approximately 15 s. There is no significant increase in merging duration. From the experimental results, we found that the duration of two droplets merging on the proposed TFTA-EWOD is acceptable and comparable with that of other EWOD devices (fabricated by the authors before [33]). It should be noted that the rapid movement of droplet can accelerate the chemical reaction rate.…”
Section: Droplet Motion Experiment: Mergingsupporting
confidence: 69%
“…Under the condition that the droplets can move successfully every time they are driven, the whole merging duration is approximately 15 s. There is no significant increase in merging duration. From the experimental results, we found that the duration of two droplets merging on the proposed TFTA-EWOD is acceptable and comparable with that of other EWOD devices (fabricated by the authors before [33]). It should be noted that the rapid movement of droplet can accelerate the chemical reaction rate.…”
Section: Droplet Motion Experiment: Mergingsupporting
confidence: 69%
“…5B). Other approaches for feedback control, such as imagebased 167,168 and optic-based, 167,169,170 are also reported.…”
Section: Integrated Sensingmentioning
confidence: 99%